Exosomal proteomes as a source for biomarker discovery in Alzheimer's disease - Marçalo, Rui Filipe Santos (2021)
Exosomes are small extracellular vesicles (EVs) involved in various physiological and pathological processes. The potential of exosomes as biomarker resources for diagnostic, prognostic and even for therapeutics has intensified research in the field, supporting the potential of exosomes for biomarker discovery in several diseases, including in Alzheimer Disease (AD). This project had as main goal the identification of potential exosomal biomarker candidates in peripheral biofluids for Alzheimer’s Disease (AD). In order to do that, part of the study was to bioinformatically analyze exosomal proteomes of different peripheral biofluids, followed by a comparative study of the obtained results with an AD mimicking model. Additionally, serum samples from AD patients were analyzed by mass spectrometry (MS) and 87 potential biomarker candidates were identified. Of note, 3 proteins, IGVL1-51, IGVL2-11 and IGVL2-8, were identified exclusively in control samples, and 2 proteins, HIST1H4 and PRH1-2, were identified exclusively in AD samples. These 5 proteins may be potential exosomal biomarker candidates for AD diagnostic. Furthermore, 2 proteins, TF and KRT14, were found by both bioinformatic analysis and MS, although with ratios between 0.5 and 1, as decreased in AD. Interestingly, in this study, statistically significant differences in the size and concentration of AD exosomes were found, having AD exosomes a higher diameter but being decreased in concentration when compared to exosomes of Control samples. The identification of potential biomarker candidates for AD may be useful not only for early disease diagnosis but also to monitor disease progression, as well as for the development of new therapies for AD, which will translate in an improvement of patient’s life quality. Thus, with this study we propose a set of potential candidates for exosomal biomarkers for AD